Information security and cryptology – ICISC 2016 : 19th International Conference, Seoul, South Korea, November 30-December 2, 2016, Revised selected papers /: 19th International Conference, Seoul, South Korea, November 30-December 2, 2016, Revised selected papers. (2017) - Unknown
No abstract available